Service use and family-centred care in young people with severe cerebral palsy: a population-based, cross-sectional clinical survey. (4th December 2015) - McDowell, B. C.; Duffy, C.; Parkes, J.
Abstract: Purpose : To assess healthcare use and family perception of family-centred care in children and young adults with severe cerebral palsy (CP) within a geographical region of the UK. Method : Young people (4–27years) with severe forms of CP; Gross Motor Function Classification System levels IV and V, were recruited via an established case register. Data were collected in the participant's home using a standardised background proforma and validated questionnaires. The Measure of Processes of Care was used to assess the family's perception of family-centred care. Results : One-hundred and twenty-three children, young people and their families/guardians participated. Results showed high accessing of specialist services in childhood with a considerable decrease in young adults. Use of generalist services remained relatively constant. The reported use of formal respite services and support groups/youth clubs was relatively poor. Family-centred care was poor in the area of "providing general information" (2.8 ± 1.73) but more moderate in the areas of "providing specific information about the young person" (4.2 ± 1.94), "enabling and partnership" (4.2 ± 1.9), "co-ordinated and comprehensive care" (4.3 ± 1.95) and "respectful and supportive care" (4.7 ± 1.75). Conclusions : The accessing of specialist services and respite care notably decreases amongst adolescents with severe forms of CP and the perception of family-centred care amongst families was fair at best. In particular, the results highlight the need for families to be provided with more general information and advice. Implications for Rehabilitation: In a quest to enhance the rehabilitation process in young people with severe forms of cerebral palsy: Commissioners and service providers need to a adopt a more rationalised, needs led approach to service provision across the lifespan of people with severe forms of cerebral palsy, to include an effective and efficient transitional period. Habilitation specialists working with young adults need to continue to recognise the importance of family-centred care in managing this complex and chronic condition. Professionals working within the healthcare system must provide better communication and improve their dissemination of information to the families of children and young people with complex needs.